Paddy rice productivity and profitability in Myanmar: Assessment of the 2022 monsoon season - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
We analyze paddy rice productivity and profitability data for the monsoon season of 2022 from the Myanmar Agriculture Performance Survey (MAPS), fielded in the beginning of 2023. The survey covered plots of 3,076 paddy rice producers, spread across all states/regions of the country. We find that: 1. Paddy rice productivity – tons of paddy produced per unit of cultivated land – at the national level decreased on average by 7.5 percent during the monsoon of 2022 compared to the monsoon of 2021. The lower productivity is mostly explained by adverse weather conditions, with negative impacts of droughts during the monsoon of 2022. Lower input use and other factors - such as increased insecurity - played an important role as well. Paddy rice yields were lowest in Kayah and Chin, two conflict-affected states. 2. Prices for most inputs used in paddy rice cultivation increased significantly between these two seasons. Prices of urea, the most important chemical fertilizer used by paddy rice farmers, increased by 87 percent on average while mechanization costs increased by 27 percent. Small decreases are noted, on average, in the use of paddy rice inputs over the last two monsoons. Despite the large price increases for chemical fertilizer, its use declined only by 8 percent compared to the previous monsoon. 3. Paddy prices at the farm level increased by 81 percent, reflecting changes in international rice prices as well as the depreciation of the MMK. Gross revenues per acre increased in nominal terms by 67 percent, mostly due to these high price increases. 4. Real profits, with nominal prices corrected by the change in the cost of an average food basket, from paddy rice farming during the monsoon of 2022 increased by 26 percent and 10 percent compared to the monsoon of 2021 and 2020 respectively. While nominal profits for paddy rice farmers increased by 95 percent over the last two seasons, price inflation has been high in the country and real profit increased much less. While the rice sector demonstrated resilience in the country, the current situation is concerning given productivity declines and high price increases, raising fears for increased food insecurity in the country. We have found improved farm profitability this year and as fertilizer prices for the coming monsoon (the monsoon of 2023) are down (due to international price decreases) and international rice prices are up (due to lower global stocks), this might further improve profitability - and incentives - for paddy production in 2023. These price developments might possibly reverse the declining productivity trend. The big unknowns that might impact paddy production in 2023 though are the weather - with less rainfall expected due to El Niño conditions in the second half of the year - and the evolution of conflict-related insecurity in the country.